Microglial adenosine A2A receptor in the paraventricular thalamic nucleus regulates pain sensation and analgesic effects independent of opioid and cannabinoid receptors - Cao, Yiping; Wu, Zhou; Zhang, Moruo; Ji, Ran; Zhang, Hongxing; Song, Lingzhen (Frontiers in Pharmacology, 2024)
IntroductionThe paraventricular thalamic nucleus (PVT) is recognized for its critical role in pain regulation, yet the precise molecular mechanisms involved remain poorly understood. Here, we demonstrated an essential role of the microglial adenosine A2A receptor (A2AR) in the PVT in regulating pain sensation and non-opioid analgesia.Method and resultsSpecifically, A2AR was predominantly expressed in ionized calcium binding adapter molecule 1 (Iba1)-positive microglia cells within the PVT, with expression levels remaining unchanged in mice experiencing persistent inflammatory pain induced by complete Freund’s adjuvant (CFA). Pharmacological activation of local PVT A2AR with its agonist CGS21680 induced significantly decreased 50% paw withdrawal threshold (50%PWTs) and paw withdrawal latency (PWLs), as measured by the Von Frey test and Hargreaves test in adult mice. Conversely, intra-PVT infusion of A2AR antagonist SCH58261 increased 50%PWTs and PWLs in mice; a robust analgesic effect was also observed in CFA mice with inflammatory pain. Importantly, these analgesic effects of A2AR antagonist SCH58261 were not affected by adjunctive intraperitoneal administration of naloxone or rimonabant, inhibitors of opioid receptor and cannabinoid CB1 receptor (CB1R), respectively.DiscussionOverall, these pharmacological experiments underscore an essential role of microglia-expressed A2AR with in PVT in pain sensation while revealing a novel analgesic action independent of opioid and cannabinoids receptors. Thus, these findings highlight PVT microglial adenosine A2A receptor as a promising target for novel approaches to pain modulation and future analgesic development.